Nonparametric changed segment detection in functional data - Bartkus, Karolis; Račkauskas, Alfredas (Nonlinear Analysis: Modelling and Control, 2026)
We address the epidemic change point detection problem without parametric assumptions. We propose statistics based on Cramér–von Mises-type statistic and reproducing kernel Hilbert space that iterate through all interval subsets, rescaling them to remain sensitive to both short and long epidemics. We prove limit theorems and provide quantiles for both statistics under the different parametrizations. The simulations show consistent power across a wide range of scenarios, and an application to electricity balancing prices consistently detects a market disturbance.
Keywords: epidemic change; reproducing kernel Hilbert space; Cramér–von Mises-type statistic